PENGARUH PROFESIONALISME, KOMPETENSI, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA ASN KANTOR KEMENTERIAN AGAMA KABUPATEN SITUBONDO - Tarqiyah, Urwatut; Arief, Mohammad Yahya; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2025)
Human Resource Management is a crucial component of any organization, playing a key role in managing employees to work effectively and efficiently in order to achieve organizational goals. The purpose of this study is to analyze and examine the influence of professionalism, work competence, and workload on employee performance, with job satisfaction as an intervening variable, among civil servants at the Ministry of Religious Affairs Office in Situbondo Regency. The population of this study consists of civil servants (ASN) at the Ministry of Religious Affairs Office in Situbondo Regency. The sampling technique used is saturated sampling. Data analysis and hypothesis testing were conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The direct effect hypothesis testing, carried out using SmartPLS 3.0 software, shows that professionalism has a positive but not significant effect on job satisfaction; work competence has a significant positive effect on job satisfaction; and workload also has a significant positive effect on job satisfaction. Furthermore, professionalism has a positive but not significant effect on employee performance; work competence has a positive but not significant effect on performance; and workload has a significant positive effect on performance. Job satisfaction has a significant positive effect on performance. The indirect effect hypothesis testing indicates that professionalism has a positive but not significant effect on performance through job satisfaction; work competence has a significant positive effect on performance through job satisfaction; and workload also has a significant positive effect on performance through job satisfaction.